Efektivitas Target Pembiayaan Baitul Maal Wa Tamwil Surya Gemilang Desa Sedayulawas Kecamatan Brondong Kabupaten Lamongan - Hamid, Abdul Muiz; Herianingrum, Sri (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to determine the effectiveness of targeted financing in BMT SuryaÂ Gemilang village Sedayulawas Brondong distridt of Lamongan through the financing to itsÂ customers and financial report statements, as well as the customersâ trust in taking capital.This study used a qualitative approach and descriptive case study. To collect theÂ data, this study uses purposive sampling and snowball technique. The results of this studyÂ show that the effectiveness of targeted financing is annually achieved as planned by BMTÂ Surya Gemilang. This is reflected in the provision of financing to customers and the financialÂ reports which always reach the target as well as the smooth repayment of loans byÂ customers.